Effect of Waterpipe (hookah) Smoking on Lipid Profile, Lipid Peroxidation, and Homocysteine Levels - Sidra Latif; Muniza Saeed (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: Tobacco smoke promotes atherosclerosis which is the major cause of death due to cardiovascular diseases, which include coronary artery disease, cerebrovascular disease, and peripheral arterial disease. Waterpipe smoking is one of the classical forms of tobacco smoking. The objective of our study was to examine the effect of waterpipe (hookah) smoking on serum lipid profile, homocysteine, and oxidant status in male waterpipe smokers. METHODOLOGY: The cross-sectional comparative study was performed at the Post Graduate Medical Institute at the Department of Physiology, Lahore. All 60 volunteers (30 waterpipe smokers and 30 non-smokers) participated included in the study using convenient sampling. Total cholesterol, high-density lipoprotein, low-density lipoprotein, triglyceride, homocysteine, and malondialdehyde levels were measured by the ELISA method in serum samples. Results were analyzed using SPSS. Mann-Whitney U-test (non-parametric test) was applied to compare differences between the two groups. RESULTS: Serum cholesterol (p≤0.001), low-density lipoprotein (p≤0.001), triglyceride (p=0.001), Serum Malondialdehyde (p=0.001), and homocysteine (p≤0.001) levels were higher, and the difference was statistically significant while high-density lipoprotein (p=0.003) was significantly lower in waterpipe smokers than non-smokers. CONCLUSION: This study concludes that serum cholesterol, triglyceride, LDL, homocysteine, and MDA levels increase and HDL decrease in male waterpipe smokers.